Bullied Adolescent’s Life Satisfaction: Personal Competencies and School Climate as Protective Factors - Lázaro-Visa, Susana; Palomera, Raquel; Briones, Elena; Fernández-Fuertes, Andrés A.; Fernández-Rouco, Noelia (Frontiers in Psychology, 2019)
Although adolescence has been defined as a stage of vulnerability, due to the biopsychosocial changes that happen throughout this developmental stage, it is also one of growth. Some of the core personal competencies that have been identified to promote positive development at this stage while simultaneously preventing risks are: (1) a positive sense of self, (2) self-regulation, (3) decision-making skills, (4) a moral system of belief, and (5) prosocial connectedness. There are many factors and contexts that influence adolescent development. The school climate, for example, has the capacity to promote positive development and life satisfaction, yet on the other hand, it is a context within which different forms of violence, such as bullying, can occur. The principal aim of this study, therefore, is to analyze the influence that bullying has on one’s life satisfaction, while taking into account participants’ socio-demographic characteristics (i.e., gender and developmental stage), their core personal competencies (i.e., problem solving strategies, empathy, emotional repair, self-esteem, and values), and the school climate. To obtain data, a hierarchical regression analysis was conducted with a sample of 647 Spanish students (53.3% female), ranging in age from preadolescence (10–13 years old; 60.3%) to mid-adolescence (14–18 years old; 39.7%), and belonging to diverse socio-economic contexts (15.3% rural) and schools (32.1% public). After gaining informed consent from both the participants and their parents, students completed the survey voluntarily, and under anonymity. Initially results show that gender, developmental stage, and having been bullied were predictors of participants’ levels of life satisfaction. When the core personal competencies were also considered in data analysis process, self-esteem, emotional repair, and social values were those demonstrating significant effects on one’s life satisfaction; moreover, being bullied was a significant predictor too. Finally, after taking school climate into account, only this variable as well as self-esteem and emotional repair were significant predictors of life satisfaction: the other assessed variables were no longer found to be significant predictors (i.e., gender, developmental stage, being bullied, and social values). These results have important implications for education objectives, methodologies, and school functioning: school climate, self-esteem and emotional repair seem to be particularly important for promoting student life satisfaction and for preventing the negative consequences associated with being bullied.